Effect of Training and Career Development on the Performance: Role of Work Motivation as Mediating - Arsyad, Raden Muhammad Furqon Kholist; Ikhwan HS; Sriekaningsih, Ana (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
This research to analyse the effect of training and career development on the performance of police office with work motivation as a mediating variable. The sample in this study were 85 police officers at Polresta Pangkalpinang. The data analysis technique used is SEM SMART-PLS. The results showed that training and career development had a positive and significant effect on the work motivation of Polri members. Furthermore, work motivation also has a positive and significant effect on the performance of police officer. In addition, training and career development were also found to have a positive and significant effect directly on the performance police officers. Work motivation is proven to mediate the effect of training and career development on the performance of police officers. Overall, the results of this study indicate that training, career development, and work motivation are important factors that can improve the performance of police officers at Pangkalpinang Police Station.